2011
DOI: 10.1007/s10353-011-0601-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive mitral valve surgery in the old patient

Abstract: Zusammenfassung. Grundlagen: Die minimal invasive Operation der Mitralklappe ist heute eine bewährte Alternative zur konventionellen Operation durch mediane Sternotomie. Trotzdem bleibt unklar, inwieweit die objektiven Vorteile von Kosmetik, Blutverlust, Intensivstations-und Krankenhausaufenthalt sowie Wiederaufnahme der Arbeit auch bei älteren Patienten zum Tragen kommen oder vielleicht durch zusätzliche Komplikationen mit erhöhter Morbidität und Mortalität aufgewogen werden. Darü ber hinaus bleibt die Frage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They concluded that a mini-sternotomy can be performed safely for aortic valve replacement without an increased risk of death, major complications (Khoshbin et al, 2011), a reduction in ICU stay time (Brown et al, 2009), or clinical benefit (Aybek et al, 2000). Moreover, we excluded 12 studies because they had no control groups (Loulmet et al, 1998;Mishra et al, 1999;Riess et al, 2001;Grossi et al, 2002;Onnasch et al, 2002b;Aybek et al, 2006;Martin et al, 2006;Seeburger et al, 2008;Glaubera et al, 2009;Müller et al, 2011;Reser et al, 2012), which ranged from 22 to 1339 in sample size. However, these studies, with 3085 patients in total, summarized the long-term clinical experience of ALMT, which is useful for making clinical decisions and ensuring the safety of ALMT.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that a mini-sternotomy can be performed safely for aortic valve replacement without an increased risk of death, major complications (Khoshbin et al, 2011), a reduction in ICU stay time (Brown et al, 2009), or clinical benefit (Aybek et al, 2000). Moreover, we excluded 12 studies because they had no control groups (Loulmet et al, 1998;Mishra et al, 1999;Riess et al, 2001;Grossi et al, 2002;Onnasch et al, 2002b;Aybek et al, 2006;Martin et al, 2006;Seeburger et al, 2008;Glaubera et al, 2009;Müller et al, 2011;Reser et al, 2012), which ranged from 22 to 1339 in sample size. However, these studies, with 3085 patients in total, summarized the long-term clinical experience of ALMT, which is useful for making clinical decisions and ensuring the safety of ALMT.…”
Section: Discussionmentioning
confidence: 99%